Crystal structure of the catalytic C‐lobe of the HECT‐type ubiquitin ligase E6AP. (5th February 2020) - Ries, Lena K.; Liess, Anna K. L.; Feiler, Christian G.; Spratt, Donald E.; Lowe, Edward D.; Lorenz, Sonja
Abstract: The HECT‐type ubiquitin ligase E6AP (UBE3A) is critically involved in several neurodevelopmental disorders and human papilloma virus‐induced cervical tumorigenesis; the structural mechanisms underlying the activity of this crucial ligase, however, are incompletely understood. Here, we report a crystal structure of the C‐terminal lobe ("C‐lobe") of the catalytic domain of E6AP that reveals two molecules in a domain‐swapped, dimeric arrangement. Interestingly, the molecular hinge that enables this structural reorganization with respect to the monomeric fold coincides with the active‐site region. While such dimerization is unlikely to occur in the context of full‐length E6AP, we noticed a similar domain swap in a crystal structure of the isolated C‐lobe of another HECT‐type ubiquitin ligase, HERC6. This may point to conformational strain in the active‐site region of HECT‐type ligases with possible implications for catalysis. Significance Statement: The HECT‐type ubiquitin ligase E6AP has key roles in human papilloma virus‐induced cervical tumorigenesis and certain neurodevelopmental disorders. Here, we present a crystal structure of the C‐terminal, catalytic lobe of E6AP, providing basic insight into the conformational properties of this functionally critical region of HECT‐type ligases.